Pengaruh Integrated Reporting Quality, Capital Structure, dan Profitability terhadap Firm Value dengan Financial Transparency sebagai Variabel Mediasi Pada Perusahaan Properti yang Terdaftar pada BEI Tahun 2020-2024 - Naila Syifa Azahra; Olivia Lovina Hermanto; Sinta Tri Hapsari; Chava Annastasia Candra; Maria Yovita R.Pandin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to examine the effect of Integrated Reporting Quality (IRQ), capital structure, and profitability on firm value, with Financial Transparency as a mediating variable in property companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study employs panel data from five selected firms (SMRA, APLN, CTRA, ASRI, and LPCK), resulting in 25 observations. Data analysis is conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The direct effect results indicate that capital structure has a negative and significant effect on firm value (β = −0.262; t = 2.891; p = 0.004), while IRQ (β = 0.126; p = 0.424) and profitability (β = 0.165; p = 0.261) show no significant effect. Financial Transparency has a negative and significant effect on firm value (β = −0.651; t = 12.087; p < 0.001) but does not mediate the relationships, as all indirect effects include zero in their confidence intervals. The model explains 52.5% of variance (R² = 0.525), indicating moderate explanatory power.